A study on gender related differences in oxidative stress status - Sardar, MMR; Ali, MOI; Pervin, F; Yeasmin, F; Ahmed, N; Latif, SA (Mediscope, 2018)
Female lives longer than male and incidence of cardiovascular disease is lower in young female. However the role of oxidative stress has been repeatedly described in various diseases but rarely healthy people. The objective of the study was to observe the gender related differences in oxidative stress status and to show significance in alteration. This cross sectional and comparative study was carried out in the Department of Physiology, Rajshahi Medical College during the period from January 2013 to June 2014. Total 45 healthy adult subjects (25 males and 20 females) were enrolled in the study. Systematic sampling technique was used to select each study subject from students, doctors and staffs of Rajshahi Medical College. Malondialdehyde (MDA), a lipid peroxide and alpha-tocopherol, an antioxidant in plasma was measured. MDA:alpha-tocopherol ratio was used as a reliable marker of oxidative stress status. The mean plasma alpha-tocopherol concentration was significantly higher (p < 0.05) and plasma MDA: alpha-tocopherol ratio was significantly lower (p < 0.05) in female group than male group. The mean plasma alpha-tocopherol concentration was significantly higher (p < 0.05) in female group aged 18-21 years than the corresponding male group. From the results of this study, it can be concluded that oxidative stress is less in female than in male indicating presence of potent compensatory response against oxidative stress in female which may be attributed to influence of female sex hormones. Mediscope Vol. 6, No. 1: Jan 2019, Page 13-18